Lingual thyroid: a case report and literature review - Gomes, Pedro (2022)
The presence of ectopic thyroid tissue at the base of the tongue is called lingual thyroid. Most cases are asymptomatic, sometimes being diagnosed accidentally, for example, in the context of an upper respiratory infection. In this paper, we present the case of a 44-year-old female patient, with a history of hypothyroidism, who came to the emergency department with fever, odynophagia, dysphagia, and right otalgia. She had edema, purulent exudate and areas of necrosis on the lingual surface of the epiglottis, ventricular and arytenoid bands; a mass was found at the base of the tongue, in the midline, above the epiglottis, with normal-appearing mucosa. Cervical computed tomography confirmed the diagnosis of supraglottitis and showed a hyperdense nodular image with uptake of contrast product at the base of the tongue, consistent with lingual thyroid; in the usual topography of the thyroid, only a small nodular image was identified. The Tc99 scintigram confirmed the diagnosis of lingual thyroid, with a larger nodular image in the oropharynx and a small one in the thyroid topographic area.